2020
DOI: 10.3390/polym12051012
|View full text |Cite
|
Sign up to set email alerts
|

Sound-Absorption Coefficient of Bark-Based Insulation Panels

Abstract: The objective of this study was to investigate the sound absorption coefficient of bark-based insulation panels made of softwood barks Spruce (Picea abies (L.) H. Karst.) and Larch (Larix decidua Mill.) by means of impedance tube, with a frequency range between 125 and 4000 Hz. The highest efficiency of sound absorption was recorded for spruce bark-based insulation boards bonded with urea-formaldehyde resin, at a level of 1000 and 2000 Hz. The potential of noise reduction of larch bark-based panels glued with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 54 publications
(64 reference statements)
1
41
0
2
Order By: Relevance
“…In the study of [ 105 ], no change in formaldehyde emission in particleboard was determined in case of addition of 6% acacia bark to the core layer, on the other hand, it was markedly decreased with the ratio of bark from 12 to 25%. Other studies showed formaldehyde decrease using bark in thermal insulation panels [ 86 , 98 , 99 , 106 , 107 ].…”
Section: Resultsmentioning
confidence: 96%
“…In the study of [ 105 ], no change in formaldehyde emission in particleboard was determined in case of addition of 6% acacia bark to the core layer, on the other hand, it was markedly decreased with the ratio of bark from 12 to 25%. Other studies showed formaldehyde decrease using bark in thermal insulation panels [ 86 , 98 , 99 , 106 , 107 ].…”
Section: Resultsmentioning
confidence: 96%
“…These resins have been widely used in the production of engineered wood-based panels as a result of their numerous advantages, e.g., low press temperatures, short press times, excellent strength properties, chemical versatility, and a relatively low price [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The main drawback of UF resins, apart from their lower water resistance in comparison with phenol and melamine formaldehyde resins [ 31 ], is the release of hazardous volatile organic compounds (VOC) and free formaldehyde from the final UF-bonded products, especially with indoor use [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite their numerous advantages of conventional synthetic thermosetting adhesives, such as excellent adhesion properties and water resistance, ease of handling, low curing temperature, short press times, relative cost-effectiveness, etc. [ 33 , 35 , 36 , 37 , 38 , 39 ], they have a major drawback, connected to the hazardous emission of free formaldehyde and other volatile organic compounds (VOC) from the finished wood-based panels [ 40 , 41 , 42 ], associated with environmental problems and a number of serious human health hazards, such as such as eye, skin, and nervous system irritation, skin sensitization, nausea, and even cancer [ 43 , 44 , 45 ]. In 2004, formaldehyde was reclassified as “carcinogenic to humans” (Group 1) by the International Agency for Research on Cancer [ 46 ].…”
Section: Introductionmentioning
confidence: 99%